Publicação de revistas científicas na internet: seguindo modelo SciELO - Souza, Eliana Pereira Salles de (2006)
This study describes the methodology for the publication of a scientific journal on the Internet using the SciELO Library standard. In order to include the journal on the internet a few editing, diagramming and image formatting software are required, in addition to an internet database. In this study the Scielo Library was used. The publication of journals over the Internet allows an easy and quick search of updated articles of a large array of journals. The inclusion of scientific journals on the Internet has promoted an evolution in terms publication, thus contributing to enhance the access of investigators and readers who may in turn accelerate spreading and obtaining scientific studies information thanks to a network with worldwide access.